Karakteristik Dakwah Nahdatul ulama (NU) - Nasiri Nasiri (STAI Syaichona Moh. Cholil Bangkalan, 2016)
NU is a religious and social organization that can not be separated from the 'ulama' and Islamic tradition. NU was born in the form of Jama'ah (community) that has been strongly bound by social and religious tradition that has its own character. NU fought whole heartedly to rescue the people in the field of propaganda, education, social, and political. NU's main characteristics of propaganda is to understand the reality of the socio-religious and socio-Islam, using the approaches of sociology (sosiulujiyyah), anthropology (antrufulujiyyah), culture (thaqafiyyah), and history (tarikhiyyah). NU is used as a Mecca of Islam throughout the world, both in terms of nationalism and in terms morality. In the propaganda system, NU Prophet and the Companions of the Prophet adopted an elegant, polite, communicative culture and tradition, and not against the current. NU then and now, even in the times to come, remain committed to deliver teachings of the Prophet and his companions' tradition.